SISTEM INFORMASI PRESENSI MAHASISWA MAGANG BERBASIS WEBSITE PADA PT KIMIA FARMA TBK - Gilang Akbar Panggulu (2022)
Attendance is a data collection activity to find out the number of participants present. Management of attendance in a company is needed. However, in the attendance management process, there are several obstacles such as the risk of human error or duplicate data caused by the management process still using a manual system through excel data input. PT Kimia Farma Tbk still uses a manual system in the process of managing student internship attendance. Therefore, in line with technological advances, a student internship attendance information system at PT Kimia Farma Tbk is needed to achieve effectiveness and efficiency in the attendance management process. This research uses Agile method with Extreme Programming (XP) Model, and is assisted by Unified Modelling Language (UML) modeling. This research is expected to produce a student internship attendance information system at PT Kimia Farma Tbk so as to facilitate the process of managing attendance to be more accurate.